Exercise intensity does not influence the efficacy of eccentric exercise as a behavioural adjuvant to vaccination - Edwards, Kate M.; Campbell, John P.; Ring, Christopher; Drayson, Mark T.; Bosch, Jos A.; Downes, Charlotte; Long, Joanna E.; Lumb, Josephine A.; Merry, Alex; Paine, Nicola J.; Burns, Victoria E. (Brain, behavior and immunity, 2010)
Acute exercise prior to vaccination can improve the antibody response to influenza vaccination. However, both the optimal exercise protocol and the mechanisms underpinning this adjuvant effect remain unclear. The aim of the current study was to determine whether exercise intensity influenced the efficacy of the intervention. One hundred and sixty healthy young adults were randomly assigned to a resting control group or one of three intervention groups, who exercised at an intensity of 60%, 85%, or 110% of their pre-determined concentric one repetition maxima. The exercise groups performed 50 repetitions of the eccentric portion of both bicep curl and lateral raise movements. All participants then immediately received a reduced dose (50% recommended dose) influenza vaccine. Antibody titres to the three viral strains contained in the vaccine were measured at baseline and at 28days post-vaccination. Compared to the control group, exercise enhanced the antibody response to the least immunogenic of the three strains (B/Florida). In addition, the exercise groups showed an augmented response to the A/Uruguay strain compared to control; however, this effect was observed only in men. The intervention had no effect on the antibody responses to the most immunogenic strain, A/Brisbane. Finally, antibody responses were unrelated to the intensity of the exercise bout. In conclusion, our findings provide further evidence of exercise as an adjuvant to enhance vaccination responses. The results further show that responses to the low-immunogenic antigens are particularly responsive to augmentation by acute eccentric exercise.